Study of molecular variations in field isolates of Ornithobacterium rhinotracheale from respiratory infections of poultry in Rayalaseema regions of Andhra Pradesh: Molecular variations of Ornithobacterium rhinotracheale in poultry - Swethasri P.; Nagendra Reddy T.; Vijayalakshmi S.; Anand Kumar A. (Indian Journal of Poultry Science, 2025)
The respiratory diseases are the most frequent causes of death and morbidity in chicken, which leads to significant financial losses to poultry farmers and industry. In the present study was aimed to isolate, identify and study of molecular variations in one of the common respiratory bacteria, Ornithobacterium rhinotracheale(ORT), is difficult bacterium to grow in lab and is the emerging pathogen. A total of 107 oral swabs ,107 tracheal swabs, 107 nasal swabs, 18 tracheal tissues, 22 exudates from infra orbital sinuses, 6 larynx and 24 lung tissue samples were collected from 18 suspected poultry farms, located in Rayalaseema region of Andhra Pradesh and these samples were cultured and then molecular detection was done by targeting 16S rRNA gene. Out of 18 farms screened 14(77.77%) farms were found positive. Among the 14 positive farms, 52 oral swabs, 58 nasal swabs, 56 tracheal swabs, 6 infra orbital sinus exudates, 4 tracheal tissues were positive with positivity of 48.6, 54.2, 52.3, 27.2, 22.2 % respectively and all 24 lung tissues and 6 larynx tissues were found to be negative. The ORT was isolated from the clinical samples by streaking on selective blood agar with gentamicin. The organism was confirmed phenotypically by cultural, biochemical tests and genotypically by targeting 16S rRNA gene. The gene products of representative samples were sent to sequencing. The obtained nucleotide sequences were verified by National Center for Biotechnology Information- Basic Local Alignment Search Tool (NCBI-BLAST) showed homology of 97.96- 98.37%. The clinical ORT isolates showed 11 nucleotide substitution at G6C, C7G, T22, T27C, A30T, A32T, G33C, A36G, G95A, T352C and A728T. OP919604 isolate showed 4 nucleotide substitution at G3T, T4G, G6A and G33A. OP919610 isolate showed single nucleotide substitution at G33A. OP919613 showed 8 nucleotide substituitons at G74T, G80A, A81G, T140C, A149G, A199T, C507T and A723C. Phylogenetic tree reveals, three present isolates (OP919513, OP919604, OP919610) segregated into close group with KY809801 ESV-301 strain of Mexico and the sequences OP919513 and OP919604 clustered into a distinct clade. The isolate OP919613 segregated in distinct clade with HF548215 B293-2B strain of United Kingdom (UK).